Effects of Lycium barbarum Polysaccharide on Endoplasmic Reticulum Stress and Oxidative Stress in Obese Mice - Yang, Feng-Lian; Wei, Yu-Xia; Liao, Bi-Yun; Wei, Gui-Jiang; Qin, Hai-Mei; Pang, Xiao-Xia; Wang, Jun-Li (Frontiers in Pharmacology, 2020)
Background The incidence of obesity-associated decline in male fertility has increased over the years. Lycium barbarum polysaccharide (LBP), a natural plant polysaccharide extracted from the Chinese herb L. barbarum has shown promising therapeutic effects in overcoming the same. Aim This study aimed to investigate the protective effect of LBP on the testes of obese mice. Methods Following administration of LBP to high-fat diet-induced obese mice for 35 days, serum, sperm, and testis samples were obtained for subsequent experiments. Biochemical analysis and sex hormone content determination were performed to observe changes in glycolipid metabolism and testosterone levels, respectively, in the blood. Hematoxylin and eosin staining were carried out to assess the pathological changes in the testicular tissue. Oxidative stress levels were detected using enzyme-linked immunosorbent assay and expression levels of endoplasmic reticulum stress markers were determined using western blot in the testicular tissue. Results Our results suggested that LBP reduced glucose levels and insulin resistance, increased testosterone levels and insulin sensitivity, and decreased testicular oxidative stress and pathological damage in obese mice. In addition, LBP down-regulated the expression of p-eIF2α, GRP78, and CHOP in the testicular tissues of obese mice. Conclusion Our results show that LBP is a potential novel drug for preventing male infertility caused by obesity.